Development of biobased films incorporated with an antimicrobial agent and reinforced with Stipa obtusa cellulose microfibers, via tape casting - Carolina Parada-Quinayá; Karen Garces-Porras; Elena Flores (Results in Materials)
In this study, chuño starch films were elaborated using acid hydrolysis, which was incorporated with different concentrations of eucalyptus essential oil (EEO). The reinforcement of the films was made by adding microfibers of Stipa obtusa (MFSO), a native Peruvian natural fiber rich in cellulose. The films were produced through the tape casting technique. The barrier properties presented swelling and solubility values of 1.478 and 0.439 g/g, respectively, at an optimal ratio of 7 % starch on a dry basis. An improvement in the modulus of elasticity of the films obtained was observed by incorporating concentrations of MFSO, starting at 0.55 %, in the polymeric matrix during the synthesis process. The FTIR spectra of the control film and the films reinforced with MFSO exhibited the same bands, due to the chemical similarities between starch and cellulose; micrographs of the reinforced films showed less homogeneous and compact structures compared to the control film, this effect became more pronounced as higher concentrations of MFSO and EEO were incorporated.